Epoxy/graphene film for lifecycle self-sensing and multifunctional applications. (29th September 2020) - Han, Sensen; Meng, Qingshi; Xing, Ke; Araby, Sherif; Yu, Yin; Mouritz, Adrian; Ma, Jun
Abstract: Graphene holds promise to provide polymers with multifunctionality such as electrical conductivity. However, pristine graphene is not processable in solvent and graphene oxide even after reduction lacks sufficient electrical conductivity and compatibility with polymers. This work reported an epoxy/graphene nanocomposite film that was synthesized by a facile approach, taking advantage of unique solution-processable graphene platelets (GnPs) that had high structural integrity as reflected by electrical conductivity of 1460 S/cm. A percolation threshold of electrical conductivity was found to be 0.63 vol% for the film. GnPs at 2 vol% improved the thermal conductivity and Young's modulus of epoxy by 117% and 101%, respectively. The film was then investigated as a multifunctional sensor. It can real-time monitor its lifecycle structure health, i.e. the measurement of not only curing parameters but the initiation, localization and evolution of damages spanning from curing to the end of service life. Being sensitive to ambient environmental temperature, the film was investigated as a thermal sensor. Its performance as a strain sensor proved satisfactory through a 20, 000-cyclic fatigue test. The film not only self-sensed damage such as cracks but mapped out the corresponding locations. This methodology could lead to the development of cost-effective, high-performance sensors for life-cycle, self-sensing health monitoring for various bonding structures. Graphical abstract: The electrical response of damaged composite films for self-sensing: (a) Self damage localization and (b) crack length evaluation. Image 1